L’enseignement du français au Centre d’Enseignement Intensif des Langues "CEIL" : Analyse des besoins langagiers d’apprenants. - Bouchemaa, saoussen (Journal of Human Sciences, 2018)
This article are interested in the teaching of french in the Intensive Education Center of languages « CEIL »,it is iscribed in fild of french on a specific objectives.The aim is, to analyze the needs of learners those who are university students and those who are not students at university, taking into consideration their difficlutes in accomplishing this education. This analysis indrown a better encircle of the heterogeneous public motivation.